Education and South Koreaâ€™s New Southern Policy: Locus and Prospects - Ancho, Inero; Kim, Kyungeun; Park, Saehoon (Jurnal Studi Pemerintahan, 2021)
The dawn of South Korean President Moon Jae-inâ€™s New Southern Policy (NSP) has undeniably created drastic shifts in the regionâ€™s economic and political arena. It could be seen as South Koreaâ€™s effort to reach out to its neighbouring countries in the south through various exchanges. A study by Butsaban (2020) concludes that NSP can be considered as a foundation for Korea and a Southeast Asian nation to promote â€œco-prosperity and open up a wider horizon for cooperation.â€ Â This qualitative study employs policy document analysis as an approach. The NSP is utilized as the main document for this research. The researchers examined the NSP with respect to the locus of education as presented in the document. These are then discussed in relation to the setting and background. With these findings, the researchers identified prospects as avenues to further enhance NSP through the lens of education. Analysis of the locus of education reveals how NSP is generally heading southwards in pursuit of exchange. While education is present in some mandates, these are seen to be limited and insufficient in various contexts, mainly aimed at academic exchange and training. The researchers have identified further avenues to explore in the light of NSPâ€™s approach to education. These include education and geopolitical stability, the increasing ASEAN populace, lifelong learning, and technology transfer. These are seen to be the pressing issues faced by the ASEAN region, to which growing needs merit immediate attention.